Bathing in Glitter, Swimming in Neon Lights, Dipping in Cloudlike Ball Pits: Three Case Studies to Delve into the Instagram Museums Era - Del Pizzo, Carola (Mimesis Journal, 2024)
This article explores, from a philosophical-semiotic perspective, the quasi mass-cultural phenomenon of Instagram Museums. Unlike most critics of these museums, anchored within a museological framework, my work prioritizes, instead, a dive into the paradigms feeding the concept by drawing attention to their recurrent features. Through the help of three Italian case studies, namely, the Museum of Dreamers (Milan), the Beautiful Gallery (Bologna), and the Balloon Museum (Rome), the article examines their shared feature of the pop-up format, questioning the theoretical implications of their relationship with time and the urban space. This study aims to be the first step of a multidisciplinary inquiry that addresses the common tendency of Instagram Museums to set childlike atmospheres, offer synesthetic experiences, and embody the essence of the immersivity paradigm, starting from their unfaltering plastic ball pits.